Linking 19th century European settlement to the disruption of a seabird’s natural population dynamics - Duda, Matthew P. (Proc Natl Acad Sci U S A, 2020)
Recent estimates indicate that ∼70% of the world’s seabird populations have declined since the 1950s due to human activities. However, for almost all bird populations, there is insufficient long-term monitoring to understand baseline (i.e., preindustrial) conditions, which are required to distinguish natural versus anthropogenically driven changes. Here, we address this lack of long-term monitoring data with multiproxy paleolimnological approaches to examine the long-term population dynamics of a major colony of Leach’s Storm-petrel (Hydrobates leucorhous) on Grand Colombier Island in the St. Pierre and Miquelon archipelago—an overseas French territory in the northwest Atlantic Ocean. By reconstructing the last ∼5,800 y of storm-petrel dynamics, we demonstrate that this colony underwent substantial natural fluctuations until the start of the 19th century, when population cycles were disrupted, coinciding with the establishment and expansion of a European settlement. Our paleoenvironmental data, coupled with on-the-ground population surveys, indicate that the current colony is only ∼16% of the potential carrying capacity, reinforcing concerning trends of globally declining seabird populations. As seabirds are sentinel species of marine ecosystem health, such declines provide a call to action for global conservation. In response, we emphasize the need for enlarged protected areas and the rehabilitation of disturbed islands to protect ecologically critical seabird populations. Furthermore, long-term data, such as those provided by paleoecological approaches, are required to better understand shifting baselines in conservation to truly recognize current rates of ecological loss.